Application Development for Fall Risk Evaluation in Elderly by Village Health Volunteers Kukot Municipality Kukot Subdistrict, Lam-Luk-Ka District, Pathum Thani - Puttawanchai, Viwat; Dangkrajang, Supika; Puengtanom, Suphanan (Asian Medical Journal and Alternative Medicine, 2022)
Introduction: Falls among the elderly are an important problem. That affects to both physical and mental injuries. Preventing falls is more important than treating a fall. Therefore, it is crucial to assess the risk of falls. Objectives: To develop an application for fall-risk evaluation in elderly by village health volunteers Kukot municipality Kukot subdistrict, Lam-Luk-Ka district, Pathum Thani. Methods: This was a developmental research, consisting of the development application and the quality assessment by 4 content specialists and application experts. In this study, for evaluate the satisfaction of this application form 62 village health volunteers were convenient sampling from 31 community of Kukot municipality Kukot subdistrict. Results: The results of the quality of the applications were excellent level (4.54, 0.37). In addition, the results of evaluate the satisfaction were good level (4.47, 0.57). Conclusions: The developed application is considered po an acceptable quality. It can be used as a tool to fall risk evaluation in elderly by health personnel volunteer.